2018
DOI: 10.1111/aor.13317
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Implantation of Intra‐Aortic Balloon Pump and Extracorporeal Membrane Oxygenation Improved Survival of Patients With Postcardiotomy Cardiogenic Shock

Abstract: The aim of this study is to report the combined application of extracorporeal membrane oxygenation (ECMO) with intra‐aortic balloon pumping (IABP) in postcardiotomy cardiac shock (PCS). A total of 60 consecutive patients who received both ECMO and IABP (concomitantly 24 hours) for PCS from February 2006 to March 2017 at Fuwai Hospital were included in our study. Clinical characteristics of the patients were collected retrospectively and compared between survivors and non‐survivors. Logistic regression analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…The pigtail catheter is then connected to the venous line of the ECLS, and thus, serves as a left vent. Some studies described more successful weaning from ECLS therapy with the addition of an IABP compared to weaning without it in patients with CS, but without pVSD, 24,25 one paper even found a survival advantage compared to the weaning without IABP. 25 We could demonstrate by an animal study an impairment of the mean arterial pressure and consequently, the perfusion of the coronary arteries for retrograde ECLS perfusion in combination with IABP compared to antegrade perfusion.…”
Section: Mechanical Circulatory Support In Patients With Postinfarcmentioning
confidence: 99%
“…The pigtail catheter is then connected to the venous line of the ECLS, and thus, serves as a left vent. Some studies described more successful weaning from ECLS therapy with the addition of an IABP compared to weaning without it in patients with CS, but without pVSD, 24,25 one paper even found a survival advantage compared to the weaning without IABP. 25 We could demonstrate by an animal study an impairment of the mean arterial pressure and consequently, the perfusion of the coronary arteries for retrograde ECLS perfusion in combination with IABP compared to antegrade perfusion.…”
Section: Mechanical Circulatory Support In Patients With Postinfarcmentioning
confidence: 99%
“…However, recently, routine use of IABP or Impella after implantation of VA-ECMO was found associated with decreased pulmonary congestion and improved ECMO weaning [8,9], however data on a survival benefit of IABP use in this setting are conflicting [10]. A retrospective study has suggested that combined application of ECMO with IABP for postcardiotomy cardiogenic shock after CABG or heart transplant was associated with a favorable outcome [11]. A prospective randomized clinical trial is currently investigating whether the addition of early direct ventricular unloading using Impella decreases pulmonary congestion and leads to improved survival in cardiogenic shock patients undergoing ECMO support (NCT03431467).…”
Section: Discussionmentioning
confidence: 99%
“…Kai Chen et al of the Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, China to reported on the combined application of extracorporeal membrane oxygenation (ECMO) with intra‐aortic balloon pumping (IABP) in postcardiotomy cardiac shock (PCS) in 60 consecutive patients. ECMO was weaned successfully in 48% patients.…”
Section: Cardiac Support and Blood Pumpsmentioning
confidence: 99%